Kontribusi Penggunaan Internet Sebagai Sumber Belajar Dengan Hasil Belajar Mahasiswa Jurusan Teknik Otomotif FT-UNP - Aulia, Dedy; Martias, Martias; Sugiarto, Toto (MSI Transaction on Education, 2020)
Lack of internet use as a learning resource for students in the teaching and learning process and the lack of optimal learning outcomes achieved by students in automotive engineering. This research is an ex post facto type, which is to find out how much the contribution of internet usage as a learning resource with the learning outcomes of students of automotive engineering FT-UNP. The population in this study were the 2015 class students who were enrolled actively in the Automotive Engineering Department of UNP-FT, totaling 137 students and the sample of the study was 58 students. From the results of the study, the level of achievement of internet use as a learning resource (X) is 92.97% (very good) and the level of learning achievement (Y) is 83.95% (good). The existence of a positive and significant relationship with the correlation coefficient r count> r table (0.456> 0.254) and the significance test correlation obtained t count> t table (4.322> 2.003) at a significant level of 5%. The strength of the relationship is quite strong. Determination of determinants shows that internet usage provides significant learning outcomes of 20%.